Pengaruh Motif Berprestasi dan Partisipasi terhadap Kinerja Guru Madrasah Tsanawiyah di Kota Manado - Muhammad Anwar; Ardianto Tola; Agustini Buchari (Journal of Islamic Education Policy, 2016)
This study aims to assess and analyze (1) the level of teachers’ achievement motivation, participation, and performance, (2) the relationship between teachers’ achievement motivation, participation, and performance, and (3) the influence of teachers’ achievement motivation and participation on their performance at Madrasah Tsanawiyah in Manado. Subjects of the study encompass all 105 teachers of Madrasah Tsanawiyah, both public and private, spread in four Madrasah Tsanawiyah existing in Manado. Data are collected using questionnaires. Data are analyzed using the Z test, correlation, and regression. The results show that (1) the general level of achievement motivation, the level of participation, and the level of teachers’ performance at Madrasah Tsanawiyah in Manado is relatively high, (3) there is a significant relationship among teachers’ achievement motivation, participation, and performance, either treated separately or simultaneously; and (3) there is significant impact of achievement motivation and participation on teachers’ performance at Madrasah Tsanawiyah in Manado, either treated separately or simultaneously.